Detecting Apoptotic Cells and Monitoring Their Clearance in the Nematode Caenorhabditis elegans - Lu, Nan (2009)
Apoptosis is a genetically controlled process of cell suicide that plays an important role in animal development and in maintaining homeostasis. The nematode Caenorhabditis elegans has proven to be an excellent model organism for studying the mechanisms controlling apoptosis and the subsequent clearance of apoptotic cells, aided with cell-biological and genetic tools. In particular, the transparent nature of worm bodies and eggshells makes C. elegans particularly amiable for live cell microscopy. Here we describe a few methods for identifying apoptotic cells in living C. elegans embryos and adults and for monitoring their clearance during embryonic development. These methods are based on Differential Interference Contrast microscopy and on fluorescence microscopy using GFP-based reporters.